Correct your English errors : avoid 99% of the common mistakes made by learners of English - Collins, Tim (New York : McGraw-Hill, 2009)
Build your English skills--by learning what not to do!
1. Pronunciation and spelling -- 2. Grammar
"Highlights more than 1,000 frequent errors"--Cover
Includes indexes
Keywords: English language -- Textbooks for foreign speakers; English language -- Errors of usage; English language -- Usage